Chronic kidney disease and emotional-behavioral disorders in adolescents - Benny Sugiarto; Meita Dhamayanti; Dedi Rachmadi Sambas (Indonesian Pediatric Society, 2019)
Background Chronic kidney disease (CKD) is characterized by progressive renal injury with inevitable functional deterioration. This functional loss is usually slow, progressive, and irreversible. Chronic kidney disease profoundly influences the daily routines of pediatric patients and their families, requiring significant psychosocial adaptation by both patients and families. Objective To assess for potential associations between CKD and emotional/behavioral disorders in adolescents. Methods This cross-sectional study was done at the Pediatric Nephrology Outpatient Department, Hasan Sadikin Hospital, Bandung, West Java. The consecutive sampling included all patients who fulfilled the following criteria: (1) aged 10-18 years, (2) diagnosed with CKD at least 3 months prior to the study, and (3) whose parents provided informed consent. The Strengths and Difficulties Questionnaire (SDQ) was used to assess emotional/behavioral disorders. Socio-demographic and clinical data were collected from medical records and interviews with parents. Chi-square and Mann-Whitney tests were used in the statistical analyses. Results A total of 75 subjects with CKD participated in the study. The majority of the subjects were female (53%) and <14 years old (55%). Emotional/behavioral disorders were found in 24 subjects (32%). There were no significant correlations between age, gender, paternal and maternal education level, duration of illness, or treatment with emotional/behavioral problems. However, later stage of CKD was significantly associated with prosocial problems, based on the SDQ assessment. Conclusion Late stage CKD is significantly associated with prosocial problems of the SDQ scales.